2016
DOI: 10.1016/j.matdes.2016.02.102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the micro-scale strength and stress-strain relation of an epoxy resin

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The local critical strain (in a finite element) was estimated using inverse modelling, to fit the local strain (taking into account the stress localization) to the experimentally observed global failure strain (4.6%, for PMMA). The estimated value (local critical strain ε = 0.18) corresponds to the data observed in [28]. If the damage criterion reaches the critical value, the Young's modulus of the element is reduced by 1000 times.…”
Section: Damage Modellingsupporting
confidence: 68%
“…The local critical strain (in a finite element) was estimated using inverse modelling, to fit the local strain (taking into account the stress localization) to the experimentally observed global failure strain (4.6%, for PMMA). The estimated value (local critical strain ε = 0.18) corresponds to the data observed in [28]. If the damage criterion reaches the critical value, the Young's modulus of the element is reduced by 1000 times.…”
Section: Damage Modellingsupporting
confidence: 68%
“…Most polymer materials are ductile and show a nonlinear relationship between stress and strain. The power exponential constitutive model, as shown in Figure 5, has significant advantages in describing the nonlinear behavior of materials from plastic deformation to failure [37]. When the Tresca and von Mises yield criterion are used in material plasticity analysis, many studies have confirmed that the initial yield and post-yielding occur between those two theories' predictions [28,31].…”
Section: Stress-strain Relationship Of Pvcmentioning
confidence: 99%
“…Most polymer materials are ductile and show a nonlinear relationship between stress and strain. The power exponential constitutive model, as shown in Figure 5, has significant advantages in describing the nonlinear behavior of materials from plastic deformation to failure [37]. Therefore, the power law curve is applied to characterize the stress-st ship of PVC material as follows:…”
Section: Stress-strain Relationship Of Pvcmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the characterization of matrix materials such as epoxy resins is typically performed at the bulk scale, using the prescribed standardized test methods such as ASTM D638 [16] or ISO 527 [17]. The research into microscale (epoxy) matrix properties remains limited [3][4][5]7,18,19] although these microscale matrix properties are likely more appropriate to represent the behavior of the matrix material confined between reinforcing fibers in actual composites.…”
Section: Introductionmentioning
confidence: 99%